Cinderella Skeleton - San Souci, Robert D.; Catrow, David (Orlando, Fla. : Harcourt, 2004)
A rhyming retelling of the story of a young woman who finds her prince at a Halloween ball despite the efforts of her wicked stepmother. The main characters are skeletons.
"Voyager books."
new kids books 2024 fall.
School Library Journal, September 2000
Publisher's Weekly, September 2000
Booklist, September 2000
Kirkus Starred, September 2000
Keywords: Cinderella -- (Legendary character); Stories in rhyme; Fairy Tales & Folklore; Halloween; Holidays & Celebrations; Skeleton; Folklore; Fairy tales